CGIAR Climate Impact Area Webinar Series - Webinar 1: How can attribution science inform loss and damage? - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
As the climate changes, extreme weather events’ frequency and intensity increase. Record-breaking heat waves on land and in the ocean, drenching rains, severe floods, years-long droughts, extreme wildfires, and widespread flooding are all becoming more frequent and intense. But now, we can calculate the influence of climate change on (some) of these extreme weather events. Low agricultural yields with devastating consequences can be attributed to anthropogenic climate change thanks to large-ensemble climate data and impact modelling: this is attribution science.